2020
DOI: 10.1002/jbmr.4007
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Early Paget's Disease in SQSTM1 Mutation Carriers: Baseline Analysis of the ZiPP Study Cohort

Abstract: Mutations in SQSTM1 are strongly associated with Paget's disease of bone (PDB), but little is known about the clinical characteristics of those with early disease. Radionuclide bone scans, biochemical markers of bone turnover, and clinical characteristics were analyzed in SQSTM1 mutation carriers who took part in the Zoledronic acid in the Prevention of Paget's disease (ZiPP) study. We studied 222 individuals, of whom 54.9% were female, with mean AE SE age of 50.1 AE 0.6 years. Twelve SQSTM1 mutations were obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…In a 16-year period of follow-up in a Dutch cohort, one (12.5%) carrier of a mutation within the SQSTM1 gene developed the disease, but the bone scan was performed in this study only in participants who had raised levels of ALP or P1NP or both ( Peeters et al, 2019 ). The recent study of Cronin et al reported 20 participants (9%) carriers of a SQSTM1 mutation with asymptomatic PDB, based on bone scan only as radiographs of bones displaying uptake on bone scan were not performed in this study ( Cronin et al, 2020 ) ( Table 3 ).…”
Section: Discussionmentioning
confidence: 88%
“…In a 16-year period of follow-up in a Dutch cohort, one (12.5%) carrier of a mutation within the SQSTM1 gene developed the disease, but the bone scan was performed in this study only in participants who had raised levels of ALP or P1NP or both ( Peeters et al, 2019 ). The recent study of Cronin et al reported 20 participants (9%) carriers of a SQSTM1 mutation with asymptomatic PDB, based on bone scan only as radiographs of bones displaying uptake on bone scan were not performed in this study ( Cronin et al, 2020 ) ( Table 3 ).…”
Section: Discussionmentioning
confidence: 88%
“…We believe that a bone scan is an essential component of the proposed management pathway since our previous study demonstrated that biochemical markers of bone turnover had poor sensitivity and specificity in detecting PDB-like bone lesions in this patient group. 17 The study has also shown that a single infusion of ZA is well tolerated and that it can favourably modify the raised bone turnover that is characteristic of active disease, as reflected by bone scan appearances and biochemical markers of bone turnover.…”
Section: Discussionmentioning
confidence: 90%
“…In case high t-ALP levels are identified (or in any case of increased bone turnover), the diagnostic procedure to be followed will be the same described above, in section 4.2.3. Concerning the use of t-ALP for this specific setting, it should be, however, underlined that, albeit it represents a valuable marker, normal t-ALP levels can be also found in patients with PDB, particularly in case of monostotic forms [ 23 ], as well as in asymptomatic cases with early PDB and a positive family history [ 52 ]. In this respect, either uNTx or P1NP demonstrated a better predictive value in identifying early cases with pagetic lesions [ 52 ].…”
Section: Results and Recommendationsmentioning
confidence: 99%